1995
DOI: 10.1109/36.406677
|View full text |Cite
|
Sign up to set email alerts
|

Measuring soil moisture with imaging radars

Abstract: An empirical algorithm for the retrieval of soil moisture content and surface Root Mean Square (RMS) height from remote.ly sensed radar data was developed using scatterorneter data. The algorithm is optimized for bare surfaces and requires two co-polarized channels at a frequency between 1.5 G1lz and 11 GHz. It gives best results for kh <2.5, p, < 35% and 0230°O mitting the usually weaker hv-polarized returns makes the algorithm less sensitive to system cross-talk and system noise, simplify the calibration pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
518
0
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 943 publications
(587 citation statements)
references
References 29 publications
9
518
0
10
Order By: Relevance
“…Theoretical modeling results proved that large aboveground biomass in dense forests can decrease backscatter, due to the saturation of the free-space (or not attenuation) [42]. This decrease in the backscatter can have strong implications for the use of L-band radar data for mapping, such as severe underprediction of soil water content and aboveground biomass [8,42]. This is especially important because the soil water content and dynamics play an important role to connect soil formation factors (vegetation and topography) with soil formation processes and soil attributes.…”
Section: Potential Of Using Multispectral and Radar Data As Covariatesmentioning
confidence: 99%
“…Theoretical modeling results proved that large aboveground biomass in dense forests can decrease backscatter, due to the saturation of the free-space (or not attenuation) [42]. This decrease in the backscatter can have strong implications for the use of L-band radar data for mapping, such as severe underprediction of soil water content and aboveground biomass [8,42]. This is especially important because the soil water content and dynamics play an important role to connect soil formation factors (vegetation and topography) with soil formation processes and soil attributes.…”
Section: Potential Of Using Multispectral and Radar Data As Covariatesmentioning
confidence: 99%
“…Again, Zribi and Dechambre (2002) reported that a number of analytical models have been proposed, but the inversion approach to retrieve roughness parameters was not accurately developed. As mentioned in the literature (Oh et al 1992, Dubois et al 1995, Zribi et al 2000, Baghdadi et al 2002, Singh 2005, Zribi et al 2005a, b, Rahman et al 2007) many inversion studies for roughness parameter estimation are based on the relation between the scattering coefficient and roughness parameters. On the other hand, researchers are using alternative approaches such as the fractal and power law technique for describing natural surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…(Baghdadi et al 2002, Satalino et al 2002, Van der Wal et al 2005. A fundamental element to understand the nature of global change is the ability to model the two-way interaction between land and atmosphere (Dubois et al 1995). Again, surface roughness is a key parameter of radar backscatter models to retrieve soil information from radar images (Singh 2005, Oh and Hong 2007, Rahman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ground azimuth slope causes the polarization rotation as shown in equation (1). Unlike the SPM, the cross polarization component can be obtained using the tilted Bragg approximation as expressed in (2). The range direction slope that causes the incidence angle change was ignored since the surface power spectrum modification is independent of polarization.…”
Section: A Soil Moisture Estimation Algorithm Using the Tilted Brmentioning
confidence: 99%
“…A space-borne mission, like HYDROS, will revolutionize the global soil moisture measurement. For SAR measurements, several successful algorithms have been reported using polarimetric radar data to estimate soil moisture [1,2,3]. These algorithms were developed based on experimental data or numerical scattering data.…”
Section: Introductionmentioning
confidence: 99%